2019
DOI: 10.31686/ijier.vol7.iss11.1912
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Technological Potential of Eschweilera truncata A. C. Sm in the Amazon

Abstract: Eschweilera truncata trees, known commercially by the name of Matamatá, are abundant, widely distributed throughout the forest, and characterized by important features for forest management, but are not harvested due to the scarcity of studies of the technological attributes that would reveal their potential, such as their machining and physical properties. Otherwise such studies might contribute to the inclusion of new species in the market, strengthening the sustainability of the forest ecosystems. Given thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Araújo et al (2019), studying managed wood species in the Amazon and applying the traditional methodology, identified the predominance of wood with high density (murici, Byrsonima crispa, 0.71 g cm -3 ; piãozinho, Micrandropsis sclerorylon, 1.18 g cm -3 ). Within this range, Fróes et al (2019) found mean values of 0.77 g cm -3 for E. truncata wood by applying the same (destructive) methodology, while Nascimento et al (2017) determined the density of E. odora by NIR, obtaining mean values of 0.80 g cm -3 . In the current study the matá-matá woods were classified as high density (BD > 0.70 g cm -3 ).…”
Section: Physical and Mechanical Characterizationmentioning
confidence: 89%
See 3 more Smart Citations
“…Araújo et al (2019), studying managed wood species in the Amazon and applying the traditional methodology, identified the predominance of wood with high density (murici, Byrsonima crispa, 0.71 g cm -3 ; piãozinho, Micrandropsis sclerorylon, 1.18 g cm -3 ). Within this range, Fróes et al (2019) found mean values of 0.77 g cm -3 for E. truncata wood by applying the same (destructive) methodology, while Nascimento et al (2017) determined the density of E. odora by NIR, obtaining mean values of 0.80 g cm -3 . In the current study the matá-matá woods were classified as high density (BD > 0.70 g cm -3 ).…”
Section: Physical and Mechanical Characterizationmentioning
confidence: 89%
“…As for the cellulose/lignin connection, the correlation is negative (Fengel & Wegener 2003). Regarding the G3 wood attributes, the extractives/BD association has been explained in several studies (Nascimento et al 2017, Soares et al 2018, Fróes et al 2019, since high-density tropical forest species grow slowly in diameter, thus having time for greater deposition of compounds in the xylem (Silva & Silva 1991, Chave et al 2009). Conversely, pioneer species, which are generally fast growing, display low density and concentration of extractives (Vale et al 2010, Kilic & Niemz 2012.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
See 2 more Smart Citations
“…Given the growing pressure from national and international demand for wood for industrial use, solutions are being created to combat and reduce the rate of deforestation (FRÓES et al, 2019). One of these solutions is to use wood from naturally fallen trees (forest waste with low environmental impact).…”
Section: Introduction and Objectivesmentioning
confidence: 99%